Profil Mineral Magnesium dan Tembaga Serum Darah Sapi Bali yang Dipelihara di Lahan Tegalan - Sujani, Ni Komang Dian Sri; Piraksa, I Wayan; Suwiti, Ni Ketut Ketut (Buletin Veteriner Udayana, 2014)
This study aims to determine the mineral magnesium and copper profile in blood serum of bali cattle farmed on dry land. Samples blood serum was taken from 15 bali cattles that farmed on dry land at Kecamatan Tejakula, Buleleng-Bali. Serums was analyzed by using wet destruction was H 2 SO 4 and HNO 3 . Samples are read using by Atomic Absorpsion Spectrophotometry (AAS). The result shows that magnesium mean of 22,364 mg/l + 0, 005 mg/l, and copper mean of 0,087 mg/l + 0.001 mg/l. If this result compared to other cattle around the world, magnesium level is still in the normal range, while copper level more lower than normal level.
Keywords: Bali cattle, magnesium, copper mineral, Atomic Absorpsion Spectrophotometry.